Síntese e caracterização de complexos metálicos (CuI,CuII,CoII, PdII) derivados do ligante 2-(2-piridilselanometil)piridina - Delgado, Cássia Pereira (2018)
This work presents the synthesis and characterization of eight compounds derived from a new synthesis methodology of the 2-picolyl selonopyridine linker with metals of different hardness. All the compounds had their structure elucidated by X-ray diffraction in monocrystal, besides other characterization methods, such as infrared spectroscopy, elemental analysis and mass spectrometry. Six different complexes were obtained from the direct reaction of the ligand with metal salts, these complexes involving CuII, CuI, CoII and PdII ions. The other two complexes were obtained from the same reaction proposal, however during prolonged exposure to air, the oxidation of the ligand was observed. Among the eight compounds synthesized in this work, seven are inedited in the literature (1, 2, 2a, 2b, 3, 4 and 5). The aliphatic carbon present in the structure of the ligand under study acts as a spacer and was used to evaluate its influence on the complexation with transition metals of different hardness, in order to provide flexibility and greater stability to the complexes formed. All the compounds obtained in this work have been shown to follow a complexation trend that is in agreement with Pearson's theory of acids and bases, where hard bases such as nitrogen and oxygen atoms coordinate hard metals and soft acids like the selenium atom to metals soft. In one of the complexes obtained, compound 5 formed an organometallic with PdII, a proposed mechanism was performed in order to elucidate this behavior. Compound 1 was submitted to analysis of the behavior as a photosensitizer of TiO2 in photocatalysis tests in the production of hydrogen gas from the photolysis of the water using a simulator of sunlight. The composite 1 as it was denominated, presented satisfactory quantitative results in the evolution of H2 production, at its apex it was 79% more efficient than the commercially available comparative material, besides presenting a high optical band gap of 3.53 eV.